2013
DOI: 10.1093/europace/eus412
|View full text |Cite
|
Sign up to set email alerts
|

A case series of chronic haemodialysis patients: mortality, sudden death, and QT interval

Abstract: In a case series of HD patients, QTc was associated with total mortality and SCD. Further studies to test this hypothesis in a larger population are necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 26 publications
3
41
0
Order By: Relevance
“…In another study, no difference in the blood pressure response between high and low DCa was van found [19]. Cardiac arrhythmias are more common in patients being treated with a DCa below 2.5 mEq/L and they also increase the risk of sudden cardiac death [20,21], which may be possibly related to a prolongation of the QT interval with low DCa levels [21,22]. Interestingly, in a recent study, the authors demonstrated that a DCa of 3.5 mEq/L compared with 2.5 mEq/L was associated with an increase in the heart rate variability LF/HF ratio, denoting higher sympathetic activity when compared to low DCa [23].…”
Section: Short-and Long-term Effects Of Dca On Clinical Outcomesmentioning
confidence: 99%
“…In another study, no difference in the blood pressure response between high and low DCa was van found [19]. Cardiac arrhythmias are more common in patients being treated with a DCa below 2.5 mEq/L and they also increase the risk of sudden cardiac death [20,21], which may be possibly related to a prolongation of the QT interval with low DCa levels [21,22]. Interestingly, in a recent study, the authors demonstrated that a DCa of 3.5 mEq/L compared with 2.5 mEq/L was associated with an increase in the heart rate variability LF/HF ratio, denoting higher sympathetic activity when compared to low DCa [23].…”
Section: Short-and Long-term Effects Of Dca On Clinical Outcomesmentioning
confidence: 99%
“…Over one third of patients on hemodialysis will have a prolonged QTc interval prior to a dialysis session [11,12]. The dialysis session itself, however, has a heterogeneous effect on QTc interval; some studies have demonstrated that hemodialysis is associated with QTc prolongation [12,13], while others have found no such association [11,14]. These disparate results are likely the result of variations in patient characteristics, coexisting cardiac comorbidities, and dialysis bath electrolyte concentrations among studies [15].…”
Section: Qt Intervalmentioning
confidence: 99%
“…QTc interval was evaluated in 122 patients on chronic hemodialysis (median age 71 years, 65% male, 38% with coronary artery disease (CAD), and median LVEF 60%) [11]. Importantly, 28% of this study population was on amiodarone.…”
Section: Qt Intervalmentioning
confidence: 99%
“…Patients on dialysis (stage 5 CKD) with ICD implantation: Patients on dialysis often present with repolarization abnormalities, including a prolonged QT interval, 33) microvolt T wave alterans, 34) and abnormal T wave morphology. 35,36) Moreover, repolarization abnormalities have been associated with SCD and all-cause mortality in patients on dialysis.…”
Section: )mentioning
confidence: 99%
“…35,36) Moreover, repolarization abnormalities have been associated with SCD and all-cause mortality in patients on dialysis. 33) Patients on dialysis have a 10 to 20-fold higher risk of suffering from SCD than patients without CKD. 5) SCD is the most common cause of death in dialysis patients, accounting for 20-35% of allcause mortality in patients on dialysis.…”
Section: )mentioning
confidence: 99%